Metastatic choriocarcinoma of the kidney discovered by refractory hematuria - Ikeda, I (Hinyokika kiyo. Acta urologica Japonica, 1996)
A case of metastatic choriocarcinoma of the kidney is reported. A 34-year-old married woman was referred to our department complaining of gross hematuria, fever and loin pain. Computed tomography revealed a right renal tumor with mixed density and multiple lung metastases. We performed nephrectomy to control refractory hematuria. The histological diagnosis of the tumor was metastatic choriocarcinoma. In young women, with gross hematuria, menstrual irregularity and atypical renal tumor with multiple lung metastases, metastatic choriocarcinoma of the kidney should be suspected